Synthesis of magnetic date stone biochar for solid phase extraction of NSAIDs from water samples. (30th January 2023) - Bensghaier, Rafika; Snoussi, Aziza; Aouled Abdallah, Marwa; Latrous, Latifa; Megriche, Adel
Abstract : A new date stone biochar was synthesized and used for the first time for magnetic solid phase extraction of NSAIDs. Abstract : This study looks at the potential of using by-products as sorbents for the microextraction of nonsteroid anti-inflammatory drugs (NSAIDs) from aqueous solutions. Magnetic solid phase extraction of NSAIDs and their determination by liquid chromatography coupled to mass spectrometry were considered. Magnetic date stone biochar was synthesized and characterized by TEM/EDX, FTIR and XRD. An experimental design was applied for the optimization of the magnetic solid phase extraction process. A two-level full factorial design was used for optimizing the experimental conditions such as the extraction time, sample volume, eluent volume and adsorbent mass. The suitable conditions were 10 mL of sample solution, 4 min of extraction time, 3.5 mL of elution solvent and 10 mg of adsorbent. For the validation of linearity, the limit of detection (LOD), limit of quantification (LOQ) and precision were evaluated. The LOQ and LOD were from 0.20 to 0.37 μg L −1 and from 0.061 to 0.111 μg L −1 with inter day and intra-day precisions less than 3.2%. The recoveries of NSAIDS were higher than 92.60%. The MDSBC can be reused five times without any decrease in adsorption capacity. The results demonstrate the potential use of biochar as a new adsorbent in magnetic solid-phase extraction devices for the removal of NSAIDs in aqueous solutions.